Drs Richard Evanson (1800–1871) and Henry Maunsell (1806–1879) of Dublin and their paediatric text - Dunn, P M (Archives of disease in childhood. Fetal and neonatal edition, 2006)
The textbook on the care of children published by these two Dublin physicians in 1836 was for many years regarded as an authoritative work on this subject.The textbook on the care of children published by these two Dublin physicians in 1836 was for many years regarded as an authoritative work on this subject.